Virtual Training System For Oxygen Distribution Control Through Hardware-IN-THE-LOOP. - Granda Ortiz, Pablo Norberto (2023)
This work seeks to cover the need that most universities have at the time of doing internships, such as training their students in a great number of industrial processes, and achieving the best preparation, without having a great economy and space, for the implementation of different laboratories. For this reason, the industrial process of oxygen storage and distribution has been implemented in virtual reality, which is based on a physical process, with the following advantages: Use of little space, low cost in the implementation, presents no danger to the student and instructor, its design is based on an immersive system achieved with Unity software, the same that allows the implementation of sound, video, animation, in order to confuse the user's senses, It also interacts with different controllers such as PID, Logic Fuzzy and MPC in order to understand the operation of each control.